Risk for Major Bleeding in Patients Receiving Ticagrelor Compared With Aspirin After Transient Ischemic Attack or Acute Ischemic Stroke in the SOCRATES Study (Acute Stroke or Transient Ischemic Attack Treated With Aspirin or Ticagrelor and Patient Outcomes). Issue 10 (5th September 2017) - Easton, J. Donald; Aunes, Maria; Albers, Gregory W.; Amarenco, Pierre; Bokelund-Singh, Sara; Denison, Hans; Evans, Scott R.; Held, Peter; Jahreskog, Marianne; Jonasson, Jenny; Minematsu, Kazuo; Molina, Carlos A.; et al.
Abstract : Background: Patients with minor acute ischemic stroke or transient ischemic attack are at high risk for subsequent stroke, and more potent antiplatelet therapy in the acute setting is needed. However, the potential benefit of more intense antiplatelet therapy must be assessed in relation to the risk for major bleeding. The SOCRATES trial (Acute Stroke or Transient Ischemic Attack Treated With Aspirin or Ticagrelor and Patient Outcomes) was the first trial with ticagrelor in patients with acute ischemic stroke or transient ischemic attack in which the efficacy and safety of ticagrelor were compared with those of aspirin. The main safety objective was assessment of PLATO (Platelet Inhibition and Patient Outcomes)–defined major bleeds on treatment, with special focus on intracranial hemorrhage (ICrH). Methods: An independent adjudication committee blinded to study treatment classified bleeds according to the PLATO, TIMI (Thrombolysis in Myocardial Infarction), and GUSTO (Global Use of Strategies to Open Occluded Coronary Arteries) definitions. The definitions of ICrH and major bleeding excluded cerebral microbleeds and asymptomatic hemorrhagic transformations of cerebral infarctions so that the definitions better discriminated important events in the acute stroke population. Results: A total of 13 130 of 13 199 randomized patients received at least 1 dose of study drug and were included in the safety analysis set. PLATO major bleeds occurred in 31 patients (0.5%) on ticagrelor and 38 patients (0.6%) on aspirin (hazard ratio, 0.83; 95% confidence interval, 0.52–1.34). The most common locations of major bleeds were intracranial and gastrointestinal. ICrH was reported in 12 patients (0.2%) on ticagrelor and 18 patients (0.3%) on aspirin. Thirteen of all 30 ICrHs (4 on ticagrelor and 9 on aspirin) were hemorrhagic strokes, and 4 (2 in each group) were symptomatic hemorrhagic transformations of brain infarctions. The ICrHs were spontaneous in 6 and 13, traumatic in 3 and 3, and procedural in 3 and 2 patients on ticagrelor and aspirin, respectively. In total, 9 fatal bleeds occurred on ticagrelor and 4 on aspirin. The composite of ICrH or fatal bleeding included 15 patients on ticagrelor and 18 on aspirin. Independently of bleeding classification, PLATO, TIMI, or GUSTO, the relative difference between treatments for major/severe bleeds was similar. Nonmajor bleeds were more common on ticagrelor. Conclusions: Antiplatelet therapy with ticagrelor in patients with acute ischemic stroke or transient ischemic attack showed a bleeding profile similar to that of aspirin for major bleeds. There were few ICrHs. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01994720. Abstract : Supplemental Digital Content is available in the text.